Design and Application of Energy Management Integrated Monitoring System for Energy Storage Power Station. Issue 1 (March 2021) - Zhong, X; Jiang, Y W; Hou, K; Cai, W; Yin, H; Liu, J; Wang, Q S
Abstract: According to the characteristics of huge data, high control precision and fast response speed of the energy storage station, the conventional monitoring technology can not meet the practical application requirements. In this paper, an integrated monitoring system for energy management of energy storage station is designed. The key technologies, such as multi-module integration technology, centralized energy management control technology, high concurrency group control technology based on IEC61850 and internal interaction mechanism based on User Datagram Protocol, are described in detail. Relying on the project site of Langli energy storage station, the secondary system architecture of the energy storage station is simplified, the stability of control operation and the fast response ability of power conversion system group are improved, and the reliability of output power of the energy storage station is guaranteed.